2013
DOI: 10.3346/jkms.2013.28.3.438
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Infant Death Syndrome in Korea: A Retrospective Analysis of Autopsy-Diagnosed Cases

Abstract: This study aimed to elucidate the demographic and sleeping environmental factors associated with sudden infant death syndrome (SIDS) in Korea. The autopsy reports of all SIDS cases reported to the National Forensic Service and Seoul National University College of Medicine between 1996 and 2008 were reviewed for data collection and analysis to identify the risk factors for SIDS. Analysis of the 355 SIDS cases reported within the study period revealed that of the 168 (47.3%) cases for which sleeping position bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 27 publications
(31 reference statements)
0
14
0
Order By: Relevance
“…Bedding practices vary by child-care philosophies, sleeping habits, and home architecture [20]. A soft mattress has frequently been reported as a risk factor in Western countries and prominently included in campaigns against SIDS.…”
Section: ) Bedding Arrangements and Sleeping On The Floormentioning
confidence: 99%
See 2 more Smart Citations
“…Bedding practices vary by child-care philosophies, sleeping habits, and home architecture [20]. A soft mattress has frequently been reported as a risk factor in Western countries and prominently included in campaigns against SIDS.…”
Section: ) Bedding Arrangements and Sleeping On The Floormentioning
confidence: 99%
“…A soft mattress has frequently been reported as a risk factor in Western countries and prominently included in campaigns against SIDS. However, this factor is unlikely to be directly applicable in the Korean context, since Koreans generally prefer harder bedding such as floor-like surfaces, which makes co-sleeping easy [20]. In Western countries, people rarely sleep on the floor, and their bodies tend to be relatively large and heavy.…”
Section: ) Bedding Arrangements and Sleeping On The Floormentioning
confidence: 99%
See 1 more Smart Citation
“…The paper by Yoo et al (1) draws attention to the significant numbers of unexpected infant deaths that are occurring in shared sleeping situations. It is now well-recognized that the more comprehensively cases of unexpected infant death are investigated, the greater is the number of cases where deaths are attributed to something other than sudden infant death syndrome (SIDS) (2, 3).…”
mentioning
confidence: 99%
“…It is now well-recognized that the more comprehensively cases of unexpected infant death are investigated, the greater is the number of cases where deaths are attributed to something other than sudden infant death syndrome (SIDS) (2, 3). However, although bed sharing deaths are still often universally attributed to SIDS (1, 4), the possibility of an asphyxial mechanism of death in some cases must be recognised (5, 6). In support of this, a recent study in South Australia demonstrated that the male to female ratio in infants who died alone was approximately 2:1, as is typical of SIDS deaths.…”
mentioning
confidence: 99%